Due Process and Fair Trial in EU Competition Law The Impact of Article 6 of the European Convention on Human Rights - Teleki, Cristina (Nijhoff Studies in European Union Law, 2021)
In Due Process and Fair Trial in EU Competition Law, Cristina Teleki addresses the complex relationship between Articles 101 and 102 of the Treaty on the Functioning of the European Union and Article 6 of the European Convention on Human Rights. The book is built around the idea that big business can threaten democracy. Due process and fair trial should be central to the process of addressing bigness through competition law, by safeguarding independent decision-making and judicial review and by preventing competition authorities from growing into administrative behemoths threatening democracy from inside. To show this, the book combines a comprehensive review of the case-law of the European Court of Human Rights with insight from economics, psychology and systems theory. Readership: Lawyers and researchers interested generally in fundamental rights, EU competition law and the interplay between the two or particularly in due process, independent decision-making or judicial review.